Community Aspiration Services from Perspectives Transparency, Accountability, and Equal Rights: Study on Representatives of Java West People - Purwadewi Sundari, Ineu; Mariana, Dede; ., Muradi; Setiabudi Sumadinata, Widya (International Journal of Engineering and Technology, 2018)
This study discusses the performance of local legislative councils in serving the distribution of community aspirations in West Java, Indonesia. The performance of the board members is viewed in terms of transparency, accountability, and equality. With descriptive-qualitative methods, the review of this study found that in order to perform their functions as elected representatives, provincial council members always provided their time to serve the community. According to the fact, members of the provincial council, among others, absorb and collect the aspirations of constituents through regular working visits; accommodate and follow up on aspirations and complaints, and provide a moral and political constituency to constituents. All of that they do with transparent, accountable, and consider the equality of rights. Based on public opinion, the quality of service to the public provided by West Java Parliament is still fluctuating, meaning it is still up and down. However, it indicates the openness in its processes.Â Â